Some Properties of Certain Subclasses of Analytic Functions with Complex Order. (21st February 2012) - Wang, Zhi-Gang; Wen, Feng-Hua; Sun, Yong
Abstract : The main purpose of this paper is to derive some coefficient inequalities and subordination properties for certain subclasses of analytic functions involving the Salagean operator. Relevant connections of the results presented here with those obtained in earlier works are also pointed out.